2011
DOI: 10.4103/0028-3886.86541
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of transforaminal epidural steroid injections in lumbosacral radiculopathy

Abstract: Quality of pain relief produced by TFES was significant. Long-term quality of pain relief was better in patients with pain duration less than 6 months. Even though, the study was designed to inject the drug once, many of the patients required second injection. A further study with multiple injections at prefixed time interval might probably result in a better overall outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…[3,4] A great majority of patients presenting with low back pain complaints benefit from conservative and noninvasive modes of treatment that include bed rest, oral medications, corsets and physical therapy but one-fourth of these patients are likely to reappear at the hospital within the same year due to a relapse of the condition.Ten percent of such patients become chronic cases and 10%-15% ultimately need surgery. [1,3,[5][6][7] Of patients undergoing surgery, 20% go through another surgical procedure due to continued pain. [8] This situation has led patients to consider more effective and minimally invasive treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] A great majority of patients presenting with low back pain complaints benefit from conservative and noninvasive modes of treatment that include bed rest, oral medications, corsets and physical therapy but one-fourth of these patients are likely to reappear at the hospital within the same year due to a relapse of the condition.Ten percent of such patients become chronic cases and 10%-15% ultimately need surgery. [1,3,[5][6][7] Of patients undergoing surgery, 20% go through another surgical procedure due to continued pain. [8] This situation has led patients to consider more effective and minimally invasive treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Roy et al 22 found that transformational epidural steroid significantly reduced pain NRS and disability scores until 12 months after injection. Moreover, Turunen et al 23 examined the long-term outcome of lumbar transpedicular instrumented posterolateral fusion in patients with varied diagnoses and reported the greatest improvement in ODI and pain VAS values was in patients who had degenerative spondylolisthesis with spinal stenosis, followed by patients who had FBSS after one to three laminectomy operations, while the lowest was in patients who had adult isthmic spondylolisthesis, and they concluded that long-term outcomes of lumbar instrumented posterolateral fusion were satisfactory for > 80% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…20 Roy et al, their overall success at 24 hours was 79%, at 1 month 60%, at 6 months 58.5% and at 1 year 59%. 21 There are several factors for varied results like patient selection, technique of injection, dosage of steroid and follow up. In our study, majority of the patients who were a failure with this technique, had long duration of symptoms.…”
Section: Discussionmentioning
confidence: 99%